Biomimetic cancer cell membrane-enriched vitamin E-stapled gemcitabine-loaded TPGS micelles for pancreatic cancer therapy - Miguel Pereira-Silva; Luis Diaz-Gomez; Bárbara Blanco-Fernandez; Ana Cláudia Paiva-Santos; Francisco Veiga; Angel Concheiro; Carmen Alvarez-Lorenzo (Drug Delivery, 2025)
Pancreatic cancer (PC) is currently a leading cause of death worldwide and its incidence is expected to increase in the following years. Chemotherapy with gemcitabine (GEM) is precluded by extensive enzymatic inactivation and clearance, and the nonspecific tissue distribution contributes to unwanted systemic toxicity and tumor resistance. In this work, GEM was encapsulated in d-ɑ-tocopheryl polyethylene glycol succinate (TPGS) micelles by ‘stapling’ GEM at 4-NH2 position with vitamin E succinate (VES) through a highly stable amide bond, achieving successful GEM hydrophobization by means of a prodrug system (VES–GEM). Recurring to solvent evaporation methodology, TPGS/VES–GEM (6/1 molar ratio) micelles were prepared, optimized regarding TPGS-to-VES–GEM ratio, and characterized regarding size, surface charge, polydispersity index, morphology, drug loading, and encapsulation efficiency (EE). Furthermore, purification methods were explored together with VES–GEM release profile and stability. Lastly, cell viability and cellular uptake of the formulation were analyzed in 2D and 3D BxPC3 cell line models. TPGS/VES–GEM micelles (6/1) showed ultra-small size (∼30 nm), and remarkable EE (>95%) together with ability to retain VES–GEM for long period of time (>7 days) with high stability. The micelles demonstrated exceptional cell cytotoxic activity for concentrations of 10 and 100 µM VES–GEM (∼0% cell viability) which may be explained by concerted action of GEM, VES, and TPGS. The nanocarrier was further enriched with PC cell membrane nanovesicles, displaying size ∼150 nm, ZP ∼ −30 mV and PDI ∼0.2 to improve biointerfacing properties and targeting properties. BxPC3 cell membrane-modified TPGS/VES–GEM micelles may be attractive biomimetic nanosystem for next-generation PC therapeutics.